Pengaruh Harga dan Gaya Hidup terhadap Keputusan Pembelian Produk Imitasi di Kota Malang - Lailatul Hikmah; Wulan Dri Puspita; Shella Fitryah Anggraeni (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study aims to analyze the influence of price and lifestyle on purchasing decisions of imitation products in Malang City. The method used is a quantitative descriptive approach to describe the existing phenomenon. The independent variables are price and lifestyle, while the dependent variable is purchasing decision. Data were collected through an open questionnaire distributed to 54 respondents who have purchased imitation products in Malang City, East Java. Data analysis was conducted using multiple linear regression and hypothesis testing. The results show that price has a negative and insignificant effect on purchasing decisions, while lifestyle has a positive and significant effect. This indicates that lifestyle is a more dominant factor than price in influencing consumer purchasing decisions. This study is expected to contribute to consumer behavior theory and provide practical insights for businesses in developing more effective marketing strategies aligned with consumer preferences.